The term structure of interest rates in small open economy DSGE model - Aleš Maršál (Charles University in Prague, Institute of Economic Studies (IES), 2011)
I lay out small open economy model with nominal rigidities to study the implication of model dynamics on the term structure of interest rates. It has been shown that in order to obtain at least moderate match simultaneously of the macro and finance data, one has to introduce long-memory habits in consumption together with a large number of highly persistent exogenous shocks. These elements of the model however worsen the fit of macro data. I find that in the open economy framework the foreign demand channel allows us to match some of the data features even without including habits and a large number of exogenous shocks.
Keywords: G12; E17; 330; DSGE small open economy model; term structure of interest rates; perturbation method; second order approximation